Correction to: Trunk Reaction Time and Kinematic Changes Following Slip Perturbations in Subjects with Recurrent Low Back Pain - Sung, Paul S.; Danial, Pamela (Annals of biomedical engineering, 2020)
This erratum is to correct the results section on page 490.